2023
DOI: 10.1007/s11356-023-25406-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Impact of the COVID-19 outbreak on China’s tourism economy and green finance efficiency

Abstract: As a result of the COVID-19 pandemic, production costs have grown, while human and economic resources have been reduced. COVID-19 epidemic costs can be reduced by implementing green financial policies, including carbon pricing, transferable green certificates, and green credit. In addition, China's tourist industry is a significant source of revenue for the government. Coronavirus has been found in 30 Chinese regions, and a study is being conducted to determine its influence on the tourism business and green f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 101 publications
0
3
0
1
Order By: Relevance
“…With the improvement of green finance, the HQED showed a trend of first declining and then rising. Based on the spatial Durbin model, Zhu et al discovered that green finance's impact on local green economic efficiency is U-shaped, whereas its effect on the green economic efficiency of adjacent areas is inverted U-shaped, demonstrating a single-threshold effect in enhancing green economic efficiency [41].…”
Section: The Relationship Between Green Finance and Hqedmentioning
confidence: 99%
“…With the improvement of green finance, the HQED showed a trend of first declining and then rising. Based on the spatial Durbin model, Zhu et al discovered that green finance's impact on local green economic efficiency is U-shaped, whereas its effect on the green economic efficiency of adjacent areas is inverted U-shaped, demonstrating a single-threshold effect in enhancing green economic efficiency [41].…”
Section: The Relationship Between Green Finance and Hqedmentioning
confidence: 99%
“…The results indicated that the impact of COVID-19 on major cities was more significant compared to peripheral regions, and there was a decrease in the prevalence of non-commuting travel. It examines the ways in which older individuals in Kunming, China, adjusted their accessibility structures and travel habits in response to the COVID-19 epidemic (Hu & Zhu, 2023). The findings suggested that those over the age of 60 had difficulties while using public transportation.…”
Section: Figure 1: Overview Of Tourism Industrymentioning
confidence: 99%
“…This study examines the current literature on crisis management in the tourism sector, specifically addressing the consequences and significance of COVID-19 for the worldwide tourism industry. The research discovered that the COVID-19 pandemic presented tourism stakeholders with the chance to reconsider and reform their tourist strategies (Hu & Zhu, 2023). This included improving health and safety protocols, using digital technologies, and reinforcing cooperation and coordination efforts.…”
Section: Figure 1: Overview Of Tourism Industrymentioning
confidence: 99%
“…Es claro que se trata de un sector volátil, más aún cuando no ha sabido recuperarse a la fecha del golpe de la pandemia (Chen, 2023;Hu & Zhu, 2023). Mientras que los gobiernos han brindado estímulos económicos al sector y por ende a los prestadores de servicio, los resultados indican que, si bien los paquetes de estímulo económico contribuyen a la mejora de la recuperación del sector turístico tras la pandemia de COVID-19, esta influencia varía según el nivel de resiliencia de un país (Xue et al, 2023).…”
Section: Introductionunclassified